Antitumor Effect of Water Decoctions of Taxus Cuspidate on Pancreatic Cancer. (25th February 2014) - Qu, Chao; Chen, Zhen
Abstract : The Taxus cuspidate has been used as a traditional Chinese medicinal herb and considered to affect various physiological functions in the body for thousands of years. As we know that taxol isolated from the Taxus cuspidate has been approved for the treatment of ovarian cancer, it has also shown its antitumor abilities against other kinds of cancers. But the antitumor activity of other components which are free of paclitaxel and hydrophilic paclitaxel derivatives from Taxus cuspidate has not been fully understood. In this study, we investigated the effect of the water decoctions from the leaves of Taxus cuspidate on pancreatic cancer cell proliferation and the potential mechanism(s); though its antitumor activity and mechanism in vitro remain to be elucidated, the water soluble constituents from Taxus cuspidate could be used in clinical for cancer patients.